College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.2 - Algebra Essentials - R.2 Assess Your Understanding - Page 27: 90



Work Step by Step

RECALL: (1) $(a^m)^n=a^{mn}$ (2) $(ab)^m=a^mb^m$ (3) $a^{-m} = \dfrac{1}{a^m}, a \ne 0$ (4) $a^1 = a$ Use rule (2) above to obtain: $=(x^{-1})^3y^{3}$ Use rule (1) above to obtain $=x^{(-1)\cdot3}y^{3} \\=x^{-3}y^{3}$ Use rule (3) above to obtain $=\dfrac{1}{x^3} \cdot y^3 \\=\dfrac{y^3}{x^3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.